Clinical examination a systematic guide to physical diagnosis - Talley, Nicholas Joseph; O'Connor, Simon (Elsevier Australia, 2014)
Clinical Examination: A systematic guide to physical diagnosis', breaks down each body system into a logical framework focusing on the history, clinical examination and correlation between physical signs and disease for each system. Helping students navigate from first impressions though to the end of consultation, the text provides a patient-centric, evidence-based approach, making it the definitive resource for anyone embarking upon a medical career.